Perinatal Mortality and Morbidity in Rural West-Java, Indonesia Part I : Vital Statistics Based on Cross-Sectional Surveys - Anna Alisjahbana; R Peeters; A Meheus (Indonesian Pediatric Society, 1990)
The first part of this article gives the summary result of cross-sectional surveys conducted in 3 rural villages in West Java. It is expected that these surveys provide the researchers with more precise data on perinatal mortality and its associated causes in order to plan and implement the Tanjungsari Intervention Study (1986- 1990). This comprises a mapping and numbering survey, and a census survey. Based on a sampling frame of 7964 houses, a systematic sample (one in eleven) was drawn for the Household and for the Married Women Surveys. The survey results yield some basic demographic indicators (table 1), Occupational information and data on education. Also data on environmental health and vital statistics are presented. It is shown that the crude birth rate is 40 per thousand and that the estimated infant mortality rate reaches a figure of 120 ‰. Furthermore, during individual interviews data was collected on characteristics, attitudes habits as well as on reproductive behaviour, of all married women under 50 years of age.